2012
DOI: 10.1158/1940-6207.capr-11-0538
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Humans by Plant Glucosinolates: Efficiency of Conversion of Glucosinolates to Isothiocyanates by the Gastrointestinal Microflora

Abstract: Plant-based diets rich in crucifers are effective in preventing cancer and other chronic diseases. Crucifers contain very high concentrations of glucosinolates (GS; β-thioglucoside-N- hydroxysulfates). Although not themselves protective, GS are converted by coexisting myrosinases to bitter isothiocyanates (ITC) which defend plants against predators. Coincidentally, ITC also induce mammalian genes that regulate defenses against oxidative stress, inflammation, and DNA-damaging electrophiles. Consequently, the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
142
3
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(156 citation statements)
references
References 32 publications
9
142
3
2
Order By: Relevance
“…Although promising, results displayed significant variability in the bioavailability of the active compound. Consistent with this finding, Fahey et al found that administration of a sulforaphane-rich broccoli sprout extract to two distinct populations (Chinese and Baltimoreans) resulted in varied bioavailability between individuals in both populations, ranging from 1% to 40% (72). In a recent intervention study, the total sulforaphane metabolite concentration in plasma was the highest ( > 2 lM) at 3 h in human subjects who consumed fresh broccoli sprouts (40g) in the first phase of study, compared with that measured after administration of a commercially available broccoli supplementation in the second phase (42).…”
Section: Sulforaphane In Human Clinical Trialsmentioning
confidence: 77%
“…Although promising, results displayed significant variability in the bioavailability of the active compound. Consistent with this finding, Fahey et al found that administration of a sulforaphane-rich broccoli sprout extract to two distinct populations (Chinese and Baltimoreans) resulted in varied bioavailability between individuals in both populations, ranging from 1% to 40% (72). In a recent intervention study, the total sulforaphane metabolite concentration in plasma was the highest ( > 2 lM) at 3 h in human subjects who consumed fresh broccoli sprouts (40g) in the first phase of study, compared with that measured after administration of a commercially available broccoli supplementation in the second phase (42).…”
Section: Sulforaphane In Human Clinical Trialsmentioning
confidence: 77%
“…This idea is supported by the work of Llanos et al, who grew Lactobacillus agilis by feeding sinigrin, Table 1 (Llanos et al, 1995). One might also suggest that this could be the cause for variation in the fractional SF production in a group of individuals given a GSL source with no myrosinase present (Egner et al, 2011;Fahey et al, 2012). Here, individuals from Baltimore were found to vary in the fraction of GSL appearing as urinary ITC, from approximately 1-40% of the dose (median was 10%).…”
Section: Glucoraphanin Hydrolysis By the Lower Gut Microbiotamentioning
confidence: 80%
“…It is possible that free SF detected in plasma or urine was generated from its metabolites during sample preparation, since these metabolites are known to be unstable and to allow SF dissociation (Conaway, Krzeminski, Amin, & Chung, 2001). However, in a study of almost 100 subjects given broccoli sprout extract daily for 14 days, urinary SF was relatively consistent at 6% of the metabolites, suggesting that free SF may be naturally present in the urine (Fahey et al, 2012). One study found that, although urinary SF-NAC was preponderant throughout the full 24 h, during the first 4 h other metabolites, i.e.…”
Section: Sulforaphane Absorption and Metabolism And Excretionmentioning
confidence: 99%
“…ITCs are products of the degradation of plant glucosinolates by the enzyme myrosinase, found in plants and in microbes of the gut microbiota (17). Plants of the Brassicaceae family produce glucosinolates; these plants include mustard, wasabi, horseradish, and broccoli.…”
mentioning
confidence: 99%